Novel Possibility of Nonstandard Statistics in the Inflationary Spectrum of Primordial Inhomogeneities - León, G.; Sudarsky, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
Inflation is considered one of the cornerstones of modern cosmology. However, the account of the origin of cosmic structure, as provided by the standard inflationary paradigm, is not fully satisfactory. The fundamental issue is the inability of the usual account to point out the physical mechanism responsible for generating the inhomogeneity and anisotropy of our Universe, starting from the exactly homogeneous and isotropic vacuum state associated with the early inflationary regime. We briefly review this issue here together with the proposal to address this shortcoming in terms of a dynamical collapse of the vacuum state of the inflaton field, which has been considered in previous works. The main goal of this manuscript is to discuss certain statistical aspects associated with the collapse and its implications in the primordial spectrum, particularly those connected with the possible appearance of a novel type of unusual correlations.